(3TQM GdYhGed (B((3GdeFI(B)s - (3CHhGdNjQ YUGe GdOjf CMeO Hf eUWai Hf Ndjds; (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s ((3YHOGdQMef Hf GdMGL eMeO s)
(3ChdgG (B:s
(3hHYO, cCfj QCjJ GdWGdHjf jWdHhf TQMkG ddYhGed YHOGdbGgQ, jMd EYQGHgG s
(3BNQgG (B:s
(3hGdgGA VejQ HGQR eLQhQ GdeMd Ydi Cfg eVGa Edjg GSJYeGdgG QGLY Edi GdeFI YGed bO Je TQM GdYhGed s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs